Reconsidering rural development : feasibility study of the application of an Israeli model of rural settlement to South Africa with reference to the coloured rural area of Ebenezer - Greeff, Ronelle S.(Ronelle Sharon) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. in Town and Regional Planning) -- University of Stellenbosch, 1993.